2012
DOI: 10.1371/journal.pone.0045632
|View full text |Cite
|
Sign up to set email alerts
|

HCV and HIV Infection among Heroin Addicts in Methadone Maintenance Treatment (MMT) and Not in MMT in Changsha and Wuhan, China

Abstract: ObjectiveTo compare HCV and HIV infection among heroin addicts in MMT and not in MMT in two large cities in central China.MethodsA total of 541 heroin addicts were recruited from MMT clinics and voluntary detoxification centers in Changsha and Wuhan, China. Structured questionnaires collected data on their socio-demographics, clinical status, risk behaviors, and their knowledge of HIV. Their HIV serostatus and Hepatitis C virus (HCV) serostatus were determined by testing antibodies in blood serum.ResultsWe obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…All results are shown in Table 1. The high HCV prevalence found in the IDU is in agreement with several reports from other countries regarding the risk of injection behavior for HCV infection [1,[11][12][13]. This result is not in agreement with a previous report showing the absence of HCV infection among illegal drug users in Bucaramanga, Colombia [4] and it may be associated with the low prevalence of heroin use in the studied population (3.9%).…”
supporting
confidence: 72%
“…All results are shown in Table 1. The high HCV prevalence found in the IDU is in agreement with several reports from other countries regarding the risk of injection behavior for HCV infection [1,[11][12][13]. This result is not in agreement with a previous report showing the absence of HCV infection among illegal drug users in Bucaramanga, Colombia [4] and it may be associated with the low prevalence of heroin use in the studied population (3.9%).…”
supporting
confidence: 72%
“…The HCV antibody-positive patients in our current study cohort had a lower S -EDDP/methadone ratio, but higher plasma R -methadone concentration and might therefore benefit from R -methadone induced withdrawal prevention. This partly explains the high percentage of HCV antibody-positive patients in the MMT programs in Taiwan and in Asia [30], [31] in which HCV causes an increase in S -methadone elimination and a reduction in adverse reactions. Our current study is the first to identify that HCV infection may influence methadone metabolism, particularly S -methadone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies reported the prevalence of HCV infection in high-risk populations: ten were from China [17][18][19][20][21][22][23][24][25][26], two from Japan [27,28], two from Korea [29,30] and five from Taiwan [12,[31][32][33][34]. Among high-risk populations, the prevalence of HCV infection was higher among IDUs (48-95 % in China, Table 4).…”
Section: Prevalence Of Hcv Infection In High-risk Populationsmentioning
confidence: 99%